Solution of Nonlinear Coupled Burger and Linear Burgers Equation - Fatima, N.; Dhariwal, M. (International Journal of Engineering and Technology, 2018)
This paper applies an analytical technique, called Homotopy Perturbation Method to determine various problems of partial differential equations and coupled Burger equations in one and two dimension equations. The final conclusion confirms that the HPM is eventually useful as well as resourceful in predicting the explanation of these kind of problems and it further concludes that HPM could be a broad utilization in modern engineering complication.Â